Towards a model-driven engineering approach for trusted execution environments (2025)
As digital cities evolve, the integration of diverse services becomes critical. However, the challenge lies not so much in traditional integration platforms such as Apache Camel or Mule, but in environments in which these platforms are deployed, which may lack mechanisms to guarantee the privacy and integrity of the data. Trusted Execution Environments (TEEs) offer secure compartments in memory for the execution of code and processing of sensitive data, providing stronger protection against attacks. Among these TEE, the Morello Board has the capabilities for compartmentalized execution using the CHERI architecture. Despite its potential, development for the Morello platform is hindered by the complexity of writing secure code in C. To address this, we propose a model-driven approach that enables automatic generation of code in C for TEEs. Our methodology includes the definition of a metamodel and model using Sirius and code generation using Acceleo. This generated code is compatible with the Morello Board. Furthermore, we demonstrate the feasibility of this approach using a case study focused on the integration of secure services in the context of smart cities.